Art therapy in a Crisis Resolution/Home Treatment Team: report on a pilot project. Issue 4 (2nd October 2017) - Wright, Tim; Andrew, Tanya
ABSTRACT: Art therapy has been held to be a helpful intervention for individuals in acute mental health states. However, while many such individuals are now treated in their own homes by Crisis Resolution/Home Treatment Teams (CRHTTs), acute art therapy provision has remained hospital based. It seems possible therefore that some individuals may be missing out on a helpful intervention at a time of great distress and vulnerability. This article describes a pilot project aimed at addressing this assumed shortfall in provision. One art therapist offered an average of two sessions per week to CRHTT patients as an integrated part of their CRHTT treatment. The article describes clinical and organisational aspects of the pilot, and offers initial findings on the therapeutic process, on outcomes and on the competencies required for this type of work.